The effects of contextual group guided discovery learning on students' mathematical understanding and reasoning - Slamet Arifin; Wahyudin Wahyudin; Tatang Herman (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2020)
In this study, we examine the effect of contextual group guided discovery (CGGD) learning approach on students' mathematical understanding and reasoning. This study was conducted through a quasi-experimental method with a control group pre and post-test design. The participants of this study were two groups of 4th-grade students in Kuningan, Indonesia. Each group was comprised of 22 students (N=44). While the experimental group was conducting mathematics learning with the CGGD learning approach, the control group was conducting mathematics learning with problem-based learning (PBL). The data were collected through a test of students' mathematical understanding (TSMU) and a test of students' mathematical reasoning (TSMR) developed by researchers. The results showed that there were significant differences in the gain score of students' mathematical understanding (SMU) (U = 134.00, Z= -2.539, P = 0.011 0.05) and students' mathematical reasoning (SMR) (U = 139.500, Z= -2.412, P = 0.016 0.05) between the experimental and the control group . The gain score and post-test score of SMU and SMR on the experimental group that implemented the CGGD learning approach were significantly higher than the control group. Therefore, we conclude that the CGGD learning approach was proven influential to empower SMU and SMR.